Anti‐pyroptotic function of TGF‐β is suppressed by a synthetic dsRNA analogue in triple negative breast cancer cells. Issue 5 (4th January 2021) - Tamura, Yusuke; Morikawa, Masato; Tanabe, Ryo; Miyazono, Kohei; Koinuma, Daizo
Abstract : Development of innovative therapeutic modalities would address an unmet clinical need in the treatment of triple negative breast cancer (TNBC). Activation of retinoic acid‐inducible gene‐I (RIG‐I)‐like receptors (RLRs) such as melanoma differentiation‐associated gene 5 (MDA5) and RIG‐I in cancer cells is suggested to suppress tumor progression by inducing cell death. Transfection of polyI:C, a conventionally used synthetic double‐stranded RNA (dsRNA) analogue that activates RLRs, has been evaluated in clinical trials. However, detailed mechanisms of tumor suppression by RLRs, especially interactions with other signaling pathways, remain elusive. Here, we showed that transfection of polyI:C suppressed transforming growth factor‐β (TGF‐β) signaling in a MDA5‐ and RIG‐I‐dependent manner. We found that suppression of TGF‐β signaling by polyI:C promoted cancer cell death, which was attenuated by forced expression of constitutively active Smad3. More detailed analysis suggested that cell death by polyI:C transfection exhibited characteristics of pyroptosis, which is distinct from apoptosis. Therapeutic efficacy of polyI:C transfection was also demonstrated using a mouse model. These results indicated that intratumor administration of polyI:C and related dsRNA analogues may be promising treatments for TNBC through inhibition of the anti‐pyroptotic function of TGF‐β. Abstract : The present study provides a new perspective of the treatment of triple negative breast cancer (TNBC) through the intracellular administration of polyI:C, a ligand for retinoic acid‐inducible gene‐I‐like receptors. PolyI:C induced the pyroptosis of TNBC cells, which was enhanced by its inhibitory role on the transforming growth factor‐β (TGF‐β)‐regulated anti‐pyroptotic functions.